Political Character and Saudi Arabic Fire Diplomacy - Abbasy Haddad (GoAcademica Research & Publishing, 2020)
This paper seeks to track the political nature behind the decision of Saudi Arabia Kingdom of Saudi executes Shia cleric, Nimr Baqir Al-Nimr using speech act theory. It is not a coincidence when the execu-tion of the Nimr conducted before implementation JCPOA, reached Iran with 5+1 group and the European Union. The Saudi political action born out of political character that is both personal and tribal.This paper provides a theoretical reinforcement to the previous related research, especially Hermann Frederick Eilts about the foreign policy of Saudi Arabia, also Philip S. Khoury and Joseph Kostiner that highlights the state's formation and patterns of tribal Arab country. Tracking model of diplomacy fire that relies on oil (money) and sword (military), a bit much to contribute about the urgency of understanding the political nature, including the style of diplomacy, as large maps to analyze the political action of the actors Arab kingdom of Saud in responding to the political dynamics of regional and global.